Substrate‐Induced and Thin‐Film Phases: Polymorphism of Organic Materials on Surfaces. (21st January 2016) - Jones, Andrew O. F.; Chattopadhyay, Basab; Geerts, Yves H.; Resel, Roland
Abstract : An increase or modification of structural order in the vicinity of a solid substrate is known for a wide range of materials. For molecular materials crystallizing on a solid surface it has been observed that new polymorphic forms may exist near the interface with the substrate, which have structures different to those observed in the bulk. Such phases are termed as substrate‐induced phases (SIPs). The presence of an SIP in a compound or a class of materials can be of crucial significance in terms of their physical properties. However, the factors that drive such a process are not clearly understood or studied in depth. In this feature article, we review the current state of understanding concerning SIPs, giving examples of systems where SIPs have been observed, discussing their origins, and which questions remain to be answered. The role of the substrate in controlling the growth and subsequent structural order has been discussed in detail and the impact of polymorphism on organic electronic device properties has been addressed. Finally, the origin of SIPs has been correlated with their crystal structures and the differences with respect to the bulk structure are highlighted. Abstract : Substrate‐induced phases are polymorphs with a molecular packing distinct from the bulk, forming in the vicinity of a solid substrate. Predominantly known for organic semiconducting molecules such as pentacene, they are found to be an intrinsic material property, forming due to the inherent structural anisotropy of organic systems. Their origins may be traced to the substrate geometry and the structure of any underlying wetting or monolayers.